PENGARUH TERAPI MENULIS PENGALAMAN EMOSIONAL TERHADAP TINGKAT DEPRESI LANSIA DI PANTI WREDA DARMA BAKTI KASIH SURAKARTA - Tunjung Sri Yulianti; Ria Kurniawati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2017)
Background : a person in the elderly will experience a failure to maintain a balance ofphysiological stress conditions, resulting in increased susceptibility to depression.Socioeconomic changes and social values of society, family system shift from extendedfamily to nuclear family, industrialization culture with independent character andindividualist consider elderly as